The Holocene pollen stratigraphy of Lake Ladoga and the vegetational history of its surroundings - Delusin, Irene; Suomalainen tiedeakatemia (Annales Academiae scientiarum Fennicae, ISSN 0066-197X, 1991)
S. 5: Abstract.
Keywords: stratigrafia; kasvillisuus; historia; ilmasto; sedimentaatio; stratigrafi; vegetation; klimat; sedimentering (geologi); Laatokka; Laatokan Karjala; Ladoga; Ladogakarelen